Analysis of corrosion and scaling in high-voltage direct-current valve cooling water system. (January 2019) - Li, X W; Ding, D; Wang, L; Sun, L W
Abstract: In this paper, the problems of corrosion and scaling in the converter valve tower cooling water system based on the ± 500kV Baode HVDC transmission project with Siemens light-triggered thyristor HVDC transmission technology are analyzed in detail. The corrosion and scaling phenomenon can cause the closure or emergency shutdown of converter valves and bring potential dangers to the safe and stable operation of power grid. So far, there is no fundamental solution to this problem. Based on the investigation of scaling phenomenon of grading electrode and corrosion of thyristor aluminum alloy heat sinks, the scaling law of the grading electrode is proposed and the cause of scaling is put forward and analyzed. Some suggestions are given.